Evaluasi kualitas website e-learning UNIPA menggunakan metode Webqual 4.0 - Yang, Ester Deborah; Baisa, Lorna Yertas; Sanglise, Marlinda (Fakultas Teknologi Informasi Universitas Kristen Satya Wacana, 2024)
Computer and internet technology advancement has prompted higher education institutions to utilize online services such as e-learning in teaching and learning activities. This research aims to measure the quality of the University of Papua (UNIPA) e-learning website from the user's perspective by employing the WebQual 4.0 approach, which encompasses the dimensions of usability, information quality, service interaction, design appearance, and user satisfaction. This study is expected to obtain specific insights to enhance the effectiveness and convenience of website usage, supporting UNIPA's progress in digital education. Based on 200 student respondents, it was found that UNIPA's e-learning website excels in information quality with an average score of 4.2 and significantly influences user satisfaction. Ease of use and design appearance are also strengths, with scores of 3.9 and 3.7, respectively, and have a significant impact. However, service interaction still needs improvement, with a score of 3.4, although it has a significant influence. Overall, user satisfaction is reasonably good, with a score of 3.8, but improving service interaction needs to be addressed by UNIPA's management. These findings illustrate user needs and serve as a basis for development to enhance the efficiency and effectiveness of online learning.